The problems of openness – effective regulation of Open source software. (1st January 2012) - Huang, Mary
Open source software (OSS) is a popular and growing global phenomenon that has significantly altered the development and use of software. The OSS phenomenon has been heralded as fostering creativity and innovation, as well as representing a paradigm shift in software development that resolves the 'software crisis'. However, a closer look at the Australian legal framework that applies to OSS indicates that the current framework does not adequately deal with the legal issues transpiring from the open source phenomenon. The object of this paper is to recommend an effective means of regulating OSS. In observing both Australian and US law, this paper will conclude that adopting a modified version of the US copyright law is one way of effectively regulating OSS, which will bridge the void between Australian law and the issues posed by OSS.